Efects of muscle stretching exercises on endothelial function in adults: A systematic review (2025)
Contextualization Muscle stretching exercises could positively afect arterial function and stifness, becoming a non-pharmacological strategy with clinical and therapeutic potential. Purpose To synthesize and analyze the efectiveness of training with muscle stretching exercises on endothelial function and arterial stifness in subjects aged 17 to 64 years. Methods A systematic review of the efectiveness of interventions with randomized controlled trials was carried out. Seven electronic databases were used to identify articles. Efects of muscular stretching interventions on endothelial dysfunction and arterial stifness variables, completeness of the report, components of the physical exercise intervention, risk of bias, and quality of the evidence were assessed. Results Seven articles met the inclusion criteria, including 279 participants. Positive efects of stretching exercises on endothelial function were inconsistent across studies. The studies’ critical appraisal (CONSORT) obtained a low score. In general, the studies had an unclear or high risk of bias. Only one study was described with a higher score, ≥50%, related to reporting physical exercise interventions (Consensus on Exercise Reporting Template, CERT). The quality of evidence (GRADE: Grading of Recommendations, Assessment, Development, and Evaluations, GRADE) resulted in very low certainty of the evidence. Conclusion While the results hint at a promising efect of muscle stretching on endothelial function, the quality of the evidence is currently very low. This underscores the urgent need for enhanced study conduct and reporting to further explore this potential.